Design And Development Of Programminglearning Platform Based On Heuristicapproach In Gamification Module Withiterative And Incremental Method(case Study : Information System Major Telkomuniversity) - Adelia Chitra Sazkia; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract - e-learning usually managed with administrator. They cannot easily to edit e-learning with their perspective. The research aims to develop a platform learning based on heuristic approach focussed on gamification especially in programming algorithm course. For this platform development, it will use iterative and incremental methodology. By using the learning platform, lecturer and student can joy experience learn programming algorithm with attractive course. Keyword : Gamification, Heuristic Learning, Iterative and Incremental, Programming Algorithm